2-[(3S)-5-Oxooxolan-3-yl]isoindoline-1,3-dione - Hui Wang; Changlu Liu; Feihua Luo (Acta Crystallographica Section E, 2012)
The oxolan-2-one ring in the title compound, C12H9NO4, has an envelope conformation with the atom linking the two five-membered rings being the flap atom.